Distribution of heavy metals, hydrocarbons and hydrocarbon-degrading bacteria in freshwater sediments - Nur Afiqah, Binti Mohamad (Universiti Malaysia Sarawak (UNIMAS), 2012)
Freshwater sediments from the Batang Ai hydroelectric Dam at Lubok Antu, Sri Aman were analyzed for heavy metals, hydrocarbons and hydrocarbon-degrading bacteria content. A total of 7 sampling sites within vicinity of Batang Ai Hydroelectric Reservoir were selected for investigation. The heavy metals content in sediment was analysed using atomic absorption spectrophotometer (AAS), while the aliphatic and aromatic hydrocarbons in sediments were analyzed by gas chromatography-flame ionization detector (GC-FID). Furthermore, distribution of hydrocarbon-degrading bacteria in sediments was analyzed using molecular biological technique. Heavy metal content in sediments show varying concentrations of nickel (Ni), copper (Cu), manganese (Mn), zinc (Zn), chromium (Cr), argentum (Ag), stannum (Sn) and bismuth (Bi). The highest concentration of Ni, Cu, Mn, Zn and Cr were detected at St2, while the highest concentration of Ag and Sn wrere detected at St1 and St4, respectively. Bismuth (Bi) was only detected at St5 and St6 with concentration 4.79 and 5.28 μg/g, respectively. Lead (Pb), cadmium (Cd) and arsenic (As) was not detected in all sampling station. The aliphatic hydrocarbons were ranged from 2 - 421145 ng/g dry weights. St1 and St2 indicate the higher content of aliphatic hydrocarbons, while St3 showed the lowest n-alkanes content. The total PAHs concentration of sediments in Batang Ai Dam ranged 2 - 5958 ng/g dry weights. The PAH composition pattern in sediments of Batang Ai suggest dominance by medium to high molecular weight compounds, and the ratio of certain related PAHs indicate anthropogenic sources and natural processes. The highest number of bacterial colonies was detected at St7 with 9.9 × 105 CFU/ml. The number of bacterial colonies in sediment is higher near the jetty than other sites of Batang Ai Hydroelectric Dam. Other sediments show moderate bacterial number with the lowest bacteria count was at St3 (1.4 × 101 CFU/ml).